The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s10162-018-00707-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaural Pitch-Discrimination Range Effects for Bilateral and Single-Sided-Deafness Cochlear-Implant Users

Abstract: By allowing bilateral access to sound, bilateral cochlear implants (BI-CIs) or unilateral CIs for individuals with single-sided deafness (SSD; i.e., normal or near-normal hearing in one ear) can improve sound localization and speech understanding in noise. Spatial hearing in the horizontal plane is primarily conveyed by interaural time and level differences computed from neurons in the superior olivary complex that receive frequency-matched inputs. Because BI-CIs and SSD-CIs do not necessarily convey frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(56 citation statements)
references
References 41 publications
2
53
0
Order By: Relevance
“…Other methods exist for place matching, including finding the interaural electrode pair that yields the “best ITD” sensitivity using psychophysical testing and measurement of the binaural interaction component in the brainstem [ 43 , 44 ]. Although pitch-matching can be influenced by conditions tested and the task parameters [ 45 ], our approach usually leads to an interaural pair of electrodes that has relatively good ITD sensitivity in adults [ 41 , 44 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other methods exist for place matching, including finding the interaural electrode pair that yields the “best ITD” sensitivity using psychophysical testing and measurement of the binaural interaction component in the brainstem [ 43 , 44 ]. Although pitch-matching can be influenced by conditions tested and the task parameters [ 45 ], our approach usually leads to an interaural pair of electrodes that has relatively good ITD sensitivity in adults [ 41 , 44 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…One way to achieve this is to perform electric-acoustic pitch matching experiments where subjects compare the pitch of a CI electrode with that evoked by acoustic stimuli differing in their spectral content. Previous pitch matching studies have shown that such measurements are difficult to conduct and usually produce very variable data (Carlyon et al, 2010; Goupell et al, 2019). This variability may have several causes, including methodological limitations as well as the choice of the acoustic stimulus type.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of methods have been used in the literature to compare the pitches of electric and acoustic stimuli. These include magnitude estimation (Vermeire et al, 2008; Plant et al, 2014), the method of constant stimuli (Boex et al, 2006; Reiss et al, 2007, 2015; Goupell et al, 2019), the method of adjustment (Green et al, 2012; Rader et al, 2016; Maarefvand et al, 2017; Tan et al, 2017) and various kinds of adaptive forced-choice procedures (Reiss et al, 2007; Schatzer et al, 2014; Vermeire et al, 2015; Peters et al, 2016). Carlyon et al (2010) tested several of these methods and showed they could all be potentially contaminated by different kinds of non-sensory biases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Landsberger et al (2019) reported significantly higher musical sound quality ratings when SSD-CI participants listened with acoustic and electric hearing than with acoustic hearing alone. SSD-CI patients represent a unique patient population with which to compare auditory perception between acoustic and electric hearing within participants [e.g., inter-aural pitch matching (Vermeire et al, 2008, 2015; Goupell et al, 2019); sound quality differences between acoustic and electric hearing (Vermeire et al, 2013; Dorman et al, 2017); melodic interval distortion (Todd et al, 2017)]. SSD-CI patients would be similarly valuable for comparing harmonic interval perception between acoustic and electric hearing.…”
Section: Introductionmentioning
confidence: 99%